Evaluation of Genotype MTBDRplus and MTBDRsl Assays for Rapid Detection of Drug Resistance in Extensively Drug-Resistant Mycobacterium tuberculosis Isolates in Pakistan - Javed, Hasnain; Bakuła, Zofia; Pleń, Małgorzata; Hashmi, Hafiza Jawairia; Tahir, Zarfishan; Jamil, Nazia; Jagielski, Tomasz (Frontiers in Microbiology, 2018)
Pakistan ranks 5th among the world’s highest tuberculosis (TB) burden countries alongside the 6th among countries with the highest burden of drug-resistant TB, including multi-drug resistant (MDR)-TB. Methods for rapid and reliable drug susceptibility testing are prerequisite for the prompt institution of effective anti-TB treatment. The aim of this study was to evaluate the efficiency of Genotype MTBDRplus and MTBDRsl assays for the detection of MDR and (pre-)extensively drug-resistant (XDR-TB) isolates in Pakistan. The study included 47 pre-XDR and 6 XDR-TB isolates, recovered from as many patients from Pakistan. Conventional drug susceptibility testing was performed using the standard 1% proportion method on the Löwenstein-Jensen medium. For molecular determination of drug resistance, GenoType MTBDRplus and GenoType MTBDRsl assays (Hain Lifescience, Germany) were used. To evaluate discrepancies between conventional and molecular DST results, mutation profiling was performed by amplifying and sequencing seven genetic loci, i.e. katG, inhA, and mabA-inhA promoter, rpoB, gyrA, embB, rrs. The sensitivity of Genotype MTBDRplus was 71.7% for INH and 79.2% for RIF. Sequence analysis revealed non-synonymous mutations in 93.3% and 27.3% of isolates phenotypically resistant to INH and RIF, respectively, albeit susceptible when tested by GenoType MTBDRplus. GenoType MTBDRsl had a sensitivity of 73.6%, 64.7%, 20%, 25%, and 100% for the detection of fluoroquinolones, ethambutol, kanamycin, amikacin, and capreomycin resistance, respectively. Upon sequencing, mutations were detected in 20%, 77.8%, and all isolates phenotypically resistant to aminoglycosides, ethambutol, and fluoroquinolones, respectively, yet. declared as susceptible with GenoType MTBDRsl. Low sensitivities seriously impedes the large-scale application of the Genotype MTBDRplus and MTBDRsl assays. Unless further optimized, the currently available line-probe assays should rather be auxiliary to the conventional, phenotype-based methods in the detection of MDR- and XDR-TB in Pakistan.